The Influence of Organizational Culture and Individual Characteristics on Teacher Performance through Organizational Citizenship Behavior as an Intervening Variable - Siswadhi, Ferry; Lestari, Anggia Ayu; Yuliza, Mai; Afrianti, Fitrina (Ilomata International Journal of Management, 2025)
This study aims to examine the effect of organizational culture and individual characteristics on teacher performance, with Organizational Citizenship Behavior serving as a mediator. The research approach utilized in the article is a causal quantitative method. The sample consisted of 87 junior high school teachers from the Bukit Kerman District in Kerinci Regency, Jambi Province, and data was gathered through a questionnaire survey. The data were then analyzed using Structural Equation Modeling (SEM) with Smart PLS 3.2.9 software. The results show that both organizational culture and individual characteristics influence teacher performance, both directly and indirectly, through the mediation of Organizational Citizenship Behavior. This research contributes valuable insights into improving teacher performance by highlighting the importance of organizational culture and individual traits.